Entrenamiento Interválico de Alta Intensidad (HIIT) en pacientes con enfermedad de las Arterias Coronarias. - Dávila Barriga, Jenifer Antonella (2025)
Coronary artery disease (CAD) is an ongoing and evolving condition. The most common cause of this disease is atherosclerosis, which occurs when plaques form within the coronary arteries. These plaques are composed of cholesterol, fatty substances, calcium, and fibrin, which is a procoagulant. Clinical manifestations include ischemia, angina pectoris, acute coronary syndromes, myocardial infarction, and sudden cardiac death. Physical inactivity amplifies an individual's risk of developing several chronic diseases. Exercise is considered a means of preventing non communicable diseases (NCDs) caused by sedentary lifestyles. Several studies have proposed that HIIT may be effective in cardiac rehabilitation (CR) since it improves VO2 max, reduces morbidity and mortality rates, restores physical fitness, and improves cardiovascular fitness. The research had a documentary and bibliographic design based on collecting information from randomized clinical trials (RCTs), systematic reviews, and digital books using databases such as PubMed and Elsevier. We identified 228 articles and selected 25 relevant studies: 23 from PubMed and 2 from Elsevier. Inclusion criteria were applied as RCTs from 2014-2025, in Spanish and English, with a minimum score of 6 on the PEDro scale, while studies before 2014, with unclear results or restricted access, were excluded. In conclusion, after the various author discussions, physical training is fundamental to rehabilitation for people with CAD. Where cardiac rehabilitation (CR) aims to improve cardiorespiratory fitness. HIIT is an efficient strategy that involves alternating short periods of rest and achieving adherence to exercise, thus enhancing aerobic capacity, insulin sensitivity, blood pressure, cardiometabolic health, physical activity, functional capacity, and quality of life. The research aims to investigate the efficacy of high intensity intervallic training in patients with coronary artery disease.